Guinea pig's courtship call: cues for identity and male dominance status? - Verzola-Olivio, Paula; Ferreira, Bruna Lima; Frei, Fernando [UNESP]; Monticelli, Patrícia Ferreira (Elsevier, 2021)
Reproduction involves communication. Males usually evolve elaborate displays that may declare their qualities and attract females to mate, using signals from different modalities. Females may use cues encoded in courtship signals to evaluate males and make choices concerning their qualities. We investigated the acoustic element of the elaborate display of the small Cavia rodents, the guinea pigs, Cavia porcellus. We verified the potentiality of the courtship call (purr) to reflect male identity and social status, through variations in acoustic structure and male vocal performance. Our results suggest that the purr encodes individuality but not male dominance status. Vocal performance and purr's structural parameters differed between individuals, but there was no correlation between acoustic parameters and male dominance status. Courtship in cavies is a multimodal display, and male quality may be encoded in visual and chemical signals. This study is the first evidence of individuality in the purr. Further studies may reveal the role of each communication channel in the courting process of Cavia.
Keywords: bioacoustics; courtship; dominance; guinea pig; male quality; rodent; vocal individuality